Implications of laser shot dosage on image quality in LA-ICP-QMS imaging. Issue 1 (25th November 2020) - Šala, Martin; Šelih, Vid Simon; Stremtan, Ciprian C.; Tămaş, Tudor; van Elteren, Johannes T.
Abstract : Higher dosages in LA-ICP-QMS imaging increases image quality; especially noticeable for low elemental concentrations, and generally dominates the slight loss in spatial resolution. Abstract : In the last few years elemental imaging by laser ablation inductively coupled plasma mass spectrometry (LA-ICPMS) has advanced rapidly, both due to hardware development associated with fast aerosol transport technologies and a deeper understanding of the influence of operational parameters on the image quality. Herein we describe the effect of dosage, i.e., the number of laser pulses per pixel, on the image quality attainable by LA-ICP-QMS as illustrated by mapping of a biological (murine brain tissue) and a mineralogical (asbestos fibers) sample. The usage of higher dosages results in better S/N ratios and is crucial when elements are present at lower concentration levels, or if mapping of more than one element is required. While this potentially increases the mapping time, elemental images with higher dosages will generally be of better quality.